PERAN LPD DESA ADAT SESETAN DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA SESETAN - Ni Ketut Wardani; I Ketut Sudana; Ni Luh Putu Yesy Anggreni (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
The Village Credit Institution (LPD) of Sesetan Traditional village plays a crucial role in empowering the economy of the community in Sesetan Village. As a microfinance institution focused on providing low-interest loans, LPD Sesetan gives financial access to the community, which was previously limited by formal financial institutions. In addition, LPD also plays a role in managing funds to support various economic empowerment programs, such as financing small and medium enterprises (SMEs) and other productive activities. Through this approach, LPD of Sesetan Traditional Village contributes to improving community welfare, creating job opportunities, and strengthening the local economy. This research aims to explore the role of LPD in fostering economic growth and its impact on the community of Sesetan Village. The method used in this research is a qualitative approach with interviews and direct observation to obtain more accurate data